2002
DOI: 10.1063/1.1523143
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional rubbed liquid-crystal cells

Abstract: The alignment characteristics of the homogeneous liquid-crystal (LC) cell rubbed multidirectionally were examined. LC molecules align along an axis between two different rubbing directions. The rubbing strength, cell thickness, and ambient temperature markedly influence the final orientation of the LC molecules. The orientation of the LC molecules and the transmission of a multidirectionally rubbed cell can be controlled according to the ambient temperature. A model that assumes substrate with various groove d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The well-controlled alignment of liquid crystal (LC) molecules on a substrate surface is crucial in LC display devices, and many studies are focused on this subject. [1][2][3][4][5] Although many non rubbing processes have been attempted, such as photo alignment and ion beam alignment, the mechanical rubbing technique is still popular due to its simplicity. [6][7][8] The effect of various rubbing parameters on the orientation of the surface of polyimide has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The well-controlled alignment of liquid crystal (LC) molecules on a substrate surface is crucial in LC display devices, and many studies are focused on this subject. [1][2][3][4][5] Although many non rubbing processes have been attempted, such as photo alignment and ion beam alignment, the mechanical rubbing technique is still popular due to its simplicity. [6][7][8] The effect of various rubbing parameters on the orientation of the surface of polyimide has been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Many have observed optical retardance from the surface of rubbed polyimide, and its magnitude increases with rubbing strength. 5,9,10) These phenomena were attributed to the formation of microstructures on the surface and the possible reorientation of surface molecules upon rubbing. Thus, characterization of retardance might be important for a better understanding or a tighter control of the rubbing process, particularly for large-area panels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Previous results show that the LC orientation direction is affected by the rubbing method through the microgroove effect and stretched polymer chains on the polymer surface. [1][2][3][4][5][6][7]14,15) Previously, the alignment characteristics of multidirectionally rubbed LC cells were reported by Huang et al 16) It was proposed that the direction of the final rubbing predominantly determined the orientation of LC molecules in multidirectionally rubbed cells because the final rubbing obliterates some of the grooves produced by the first rubbing. Recently, the effects of IB irradiation and rubbing on the alignment direction and alignment mechanism of LCs on homogeneous polyimide surfaces have been reported by Lee et al 17) The LC alignment direction was shown to follow the IB irradiation alignment direction on the polyimide surface, regardless of the irradiation occurring before or after rubbing.…”
mentioning
confidence: 98%
“…To achieve a homogenous alignment, a substrate requires an additional process that induces LC directors to a preferred direction. Various methods such as rubbing, [10][11][12][13] oblique deposition of inorganic oxides such as SiO 2 , 14) use of Langmuir-Blodgett film, 15) and nonrubbing 16) for obtaining uniform alignment have been proposed. Among them, planar anchoring of the nematic director in the conventional LCD has been mainly achieved by rubbing a polymer film, polyimide (PI) that is, by generally creating microgrooves on the polymer surface and inducing surface anisotropy in molecular orientation on the surface of the polymer.…”
mentioning
confidence: 99%